Sediment Control in Irrigation Canal Intakes - Gonzales, Clarito C. (Philippine Engineering Journal, 2021)
The control of sediments at irrigation canal intakes is a universal problem in the design of irrigation diversion systems. To facilitate the solution of the problem, the sediment load is first predicted using one of the numerous analytical equations. From the computed estimate, a preliminary design of the sediments control scheme is made. However, this initial design is not necessarily the optimum scheme. In this regard, model studies serve as an aid in the evaluation of the sediment control scheme. Several model studies conducted and presently being conducted at the National Hydraulic Research Center are thus discussed to illustrate the evaluation procedure involved.